Marketing strategies after the covid-19 pandemic towards the development of indonesian tourism destinations - Digdowiseiso, Kumba (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Indonesia's tourism sector is famous worldwide as it has many tourist destinations in all countries. The government also raises the management of tourist areas through various government policies so that Indonesian tourism is increasingly advanced and recognised in the eyes of nature. This study aims to find out the marketing strategy after the co-19 pandemic for the development of Indonesian tourism destinations. The research method used in this research is qualitative. Activities in data analysis are data reduction, data presentation, and conclusion drawing or verification. The results of the literature analysis show that the authorities have provided particular policies for improving tourist areas, and various tourist destinations have also implemented strategies and programmes that can adapt to the so-called new era. There has been a change in tourist attitudes.